2017
DOI: 10.1002/gps.4789
|View full text |Cite
|
Sign up to set email alerts
|

Association of gout and depression: A systematic review and meta‐analysis

Abstract: Our meta-analysis demonstrates a positive association between gout and depression. Further large-scale prospective cohort studies are needed to investigate the causality between gout and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…During gout flares, emotional impacts were even more severe, with patients reporting despondency and frustration from their pain and immobility, compounded by the need to explain themselves to others and how others perceived their illness. These results coincide with recent research demonstrating a significant association between depressive symptoms and frequency of gout flares 22,23 . This raises questions as to how emotional wellbeing can be improved among patients with gout, potentially through mental health services, or by improving outcomes through better treatment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…During gout flares, emotional impacts were even more severe, with patients reporting despondency and frustration from their pain and immobility, compounded by the need to explain themselves to others and how others perceived their illness. These results coincide with recent research demonstrating a significant association between depressive symptoms and frequency of gout flares 22,23 . This raises questions as to how emotional wellbeing can be improved among patients with gout, potentially through mental health services, or by improving outcomes through better treatment.…”
Section: Discussionsupporting
confidence: 87%
“…These results coincide with recent research demonstrating a significant association between depressive symptoms and frequency of gout flares. 22,23 This raises questions as to how emotional wellbeing can be improved among patients with gout, potentially through mental health services, or by improving outcomes through better treatment. Demonstrating how ULTs can reduce the emotional impacts of gout may also be an avenue for improving adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Our linguistic analyses reflect greater disability in social and leisure activities and lower positive emotion for those searching for medical conditions such as gout or arthritis, compared to people who do not search for these conditions. Although it cannot be assumed that all participants searching for gout had the condition, these findings align with prior studies which have shown higher rates of depression (26), and reduced social participation in people with gout (27).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, steroid treatment for gout may induce muscle weakness and osteoporosis and increase the incidence of injury. A recent meta-analysis demonstrated a strong positive relationship between gout and depression [22]. We can reasonably speculate that the greater incidence of suicide and poisoning in gout patients is related to depressive disorders.…”
Section: Discussionmentioning
confidence: 61%